2021
DOI: 10.2478/fhort-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between salicylic acid and resistance to mite in strawberry

Abstract: The two-spotted spider mite (TSSM) Tetranychus urticae is a polyphagous pest which infests several wild and cultivated species of plants worldwide. To date, this mite is the most deleterious pest attacking the strawberry plant under a protected environment. Exogenously applied salicylic acid (SA) has been found to induce resistance to biotic and abiotic stresses. Morpho-anatomical changes in strawberry leaflets and TSSM preference tests were investigated in response to SA treatment. Plants grown in a greenhous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Currently, strawberry cultivation in the southern hemisphere is based on cultivars from international breeding programs, which leads to market dependence and vulnerability [11,30], since the cultivars are not well adapted to the climate, and they do not express their maximum genetic potential. These cultivars have low productivity in tropical and subtropical conditions, due to their lack of adaptability and stability throughout the year, especially during the warmest periods [1].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, strawberry cultivation in the southern hemisphere is based on cultivars from international breeding programs, which leads to market dependence and vulnerability [11,30], since the cultivars are not well adapted to the climate, and they do not express their maximum genetic potential. These cultivars have low productivity in tropical and subtropical conditions, due to their lack of adaptability and stability throughout the year, especially during the warmest periods [1].…”
Section: Discussionmentioning
confidence: 99%
“…Salicylic acid is a plant hormone and produced naturally in plants, and is considered a phenolic compound (Hassoon and Abduljabbar, 2020). Salicylic acid enhances plant vigor and fruit quality traits (Mohamed et al,2017, Youssef et al, 2017 and improves the strawberry plant's tolerance for different abiotic stresses such as salinity stress (Roshdy et al, 2021), drought stress (Dakheel et al, 2022), and enhanced strawberry plant resistance for biotic stresses such as gray mold disease (Emam et al, 2023) and spider mite (De Resende et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, they require careful management of nutrient and pH levels, as well as regular irrigation. Different literatures have compared the application of soil and soilless media for strawberry cultivation [ 13 , 14 ]. It is demonstrated that the fruit quality factors including pH, titrable acidity and also taste index (TSS/TA) are different in soil and soilless growing media of strawberries as the strawberries grown in soil had the maximum amount of pH, Ca, Zn, Fe, P, N, total soluble slides and taste index (TSS/TA) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%